2023
DOI: 10.1186/s13023-023-02893-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next-generation sequencing for detection of PIK3CA mutations in archival tissues from patients with Klippel–Trenaunay syndrome in an Asian population

Yuki Sasaki,
Kosuke Ishikawa,
Kanako C. Hatanaka
et al.

Abstract: Background Klippel–Trenaunay syndrome (KTS) is a rare slow-flow combined vascular malformation with limb hypertrophy. KTS is thought to lie on the PIK3CA-related overgrowth spectrum, but reports are limited. PIK3CA encodes p110α, a catalytic subunit of phosphatidylinositol 3-kinase (PI3K) that plays an essential role in the PI3K/AKT/mammalian target of rapamycin (mTOR) signaling pathway. We aimed to demonstrate the clinical utility of targeted next-generation sequencing (NGS) in identifying PIK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In this study, we have identified PIK3CA p.Asn345Lys and p.Pro449_Leu452del in FIL patients for the first time. Although PIK3CA variants at different sites might not uniformly activate the PI3K-AKT pathway to the same extent, they all result in alterations in the expression of downstream proteins [ 29 ]. Given the relatively recent introduction of the PROS, there has been limited research exploring the changes in downstream genes within the diseases it encompasses.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have identified PIK3CA p.Asn345Lys and p.Pro449_Leu452del in FIL patients for the first time. Although PIK3CA variants at different sites might not uniformly activate the PI3K-AKT pathway to the same extent, they all result in alterations in the expression of downstream proteins [ 29 ]. Given the relatively recent introduction of the PROS, there has been limited research exploring the changes in downstream genes within the diseases it encompasses.…”
Section: Discussionmentioning
confidence: 99%